The impact of the non‐classical MHC proteins HLA‐DM and HLA‐DO on loading of MHC class II molecules - Kropshofer, Harald; Hämmerling, Günter J.; Vogt, Anne B. (Immunological reviews, 2006)
Summary: Peptide binding to classical major histocompatibility complex (MHC) class II molecules is known to be determined by the properties of the class ii peptide binding groove but recently it turned out to be co‐controlled by the activity of the non‐classical MHC molecules HLA‐DM and HLA‐DO: HLA‐DM functions as a mediator of peptide exchange.
First published: 28 April 2006
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 16.02.2021